1998
DOI: 10.1111/j.1524-4725.1998.tb04226.x
|View full text |Cite
|
Sign up to set email alerts
|

Mohs Micrographic Surgery for Lentigo Maligna and Lentigo Maligna Melanoma. A Follow-up Study

Abstract: MMS using frozen and rush permanent sections resulted in a 97% cure rate for LM and LMM. Because MMS minimizes the removal of normal tissue, and the cure rate exceeds that of conventional therapies, the authors recommend this technique for the treatment of LM and LMM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
136
2
7

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 40 publications
9
136
2
7
Order By: Relevance
“…Case series have supported the efficacy of Mohs surgery for MIS, with longterm cure rates equaling or exceeding historical cure rates with conventional wide local excision. [42][43][44] In our study, more than half of all respondents reported the use of Mohs micrographic surgery in the surgical treatment of facial MIS, whereas most respondents favored traditional surgical excision for nonfacial lesions. This differential practice in treating facial vs nonfacial MIS is likely due to the finding that recurrence rates on the head and neck are especially high after local excision.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 84%
“…Case series have supported the efficacy of Mohs surgery for MIS, with longterm cure rates equaling or exceeding historical cure rates with conventional wide local excision. [42][43][44] In our study, more than half of all respondents reported the use of Mohs micrographic surgery in the surgical treatment of facial MIS, whereas most respondents favored traditional surgical excision for nonfacial lesions. This differential practice in treating facial vs nonfacial MIS is likely due to the finding that recurrence rates on the head and neck are especially high after local excision.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 84%
“…Although many authors have reported on recurrence rates, 3,9,21,24,26,27 only a few have obtained longterm (5-year) follow-up. 9,24,26 Additionally, results may not be comparable because follow-up methods are not always adequately described.…”
Section: Mohsmentioning
confidence: 99%
“…3,[24][25][26][27] However, since most recurrences of LM do not occur until 3 to 5 years after initial excision, long-term follow-up is needed to determine the success rate of any treatment modality. Although many authors have reported on recurrence rates, 3,9,21,24,26,27 only a few have obtained longterm (5-year) follow-up. 9,24,26 Additionally, results may not be comparable because follow-up methods are not always adequately described.…”
Section: Mohsmentioning
confidence: 99%
“…These other histologic types, such as lentigo maligna or dermatofibrosarcoma protuberans, are subject to much more variability in terms of MMS technique. 53,54 We therefore chose to focus on 1095 cases of nonmelanoma skin cancer treated according to standard MMS.…”
Section: Commentmentioning
confidence: 99%